Cipio'r Llyw - Schiavone, Awen (Y Lolfa, 2017)
Fifteen-year old Hywel Dafydd goes on his first voyage. Eventually he becomes captain of his own ship, and meets trouble when he meets pirates. The story takes us to Sierra Leone and to the Martinique and Barbados islands among other places. A great adventure novel. Intro – 1. Cipio´r cyfle – 2. Parhau â´r antur – 3. Draenen ddu ar y môr – 4. Amser dial – 5. Newid cwrs – 6. Dan glo – 7. Tro ar fyd – 8. Miwtini – 9. Teitl newydd – 10. Heddwch – 11. Y prae cyntaf – 12. Twyllo – 13. Ysbail o´r diwedd – 14. Gwallgofrwydd – 15. Croeso anghynnes – 16. Dryswch a methiant – 17. Cynllwynio – 18. Caer mewn crafangau – 19. Gwledd a siom – 20. Cyfeillion neu elynion? – 21. Tri gwr doeth – 22. Mewn undod mae nerth – 23. Diwedd y Drindod – 24. Llond llaw – 25. Syndod mawr! – 26. Tyfu a chryfhau – 27. Colli´r Royal James – 28. Rhwydd hynt – 29. Diwedd y gân – Llyfryddiaeth.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books